Cytomegalovirus infection among people living with HIV in Sweden : Case profiles, treatment strategies and patient outcomes at Karolinska University Hospital 2010–2020 - Xu, Xinling (Wiley-Blackwell, 2025)
Objectives: In countries with access to early antiretroviral treatment (ART), opportunistic infections caused by cytomegalovirus (CMV) in people living with HIV (PLWH) are becoming increasingly rare. As potential complications are severe, it is critical to remain aware of this important diagnosis. However, clinical characteristics and prognosis of CMV infection in PLWH in the era of modern ART have not been well described.
Methods: Here, we compiled the clinical presentation, management and outcome of CMV infection in PLWH treated at the infectious diseases clinic of Karolinska University Hospital during 2010-2020.
Results: We identified 51 cases of active CMV infection, based on detection of CMV-DNA, mainly diagnosed in patients with CD4 T-cell count <200 cells/μL (86%). Median time from HIV diagnosis to detection of CMV infection was 16 days. In 20 cases (39%), CMV infection was symptomatic with retinitis identified as a manifestation in 70% of cases. Symptomatic CMV infection was treated for 73 (20-313) days upon diagnosis, mostly using valganciclovir. One-year mortality was 22% and was associated with longer time to ART initiation from HIV diagnosis and with comorbidities, but not with CMV-DNA levels or CD4 count. Immune reconstitution was not significantly compromised in patients with symptomatic CMV, although CD4/8 ratio tended to be lower in patients with systemic CMV infection.
Conclusions: Retinitis remains the most common manifestation of symptomatic CMV infection in PLWH. Recognizing CMV infection is important, especially in the management of 'late presenters'. Adequate duration of antiviral therapy and appropriate follow-up must be ensured to avoid complications.